Raspberry Pi based Cyber physical system for driver monitoring - Ho, Jeng Hung (2023)
Nowadays, the rate of accident in Malaysia is very high. There are many factors cause the accident happened but the factor that focused on this project is the drunkenness and drowsiness of the driver. To decrease the accident rate, driver monitoring system is planned to develop in this project. The driver monitoring system is used to monitor the situation of the driver throughout the whole driving journey and reduce the occurrence of accident. The driver monitoring system contained driver authentication and monitoring functions. The microcontroller used in the driver monitoring system is Raspberry Pi 4 Model B. The camera in the system will identify and authenticate the driver before drive the car and monitor the driver. The system will produce action to notify the driver is not suitable to drive in the current situation like display warning messages on the screen, give alert for pilot and co-pilot and so on when it detects the eyes of driver closed over 4 seconds or sensed the alcohol is over 800ppm from the gas sensor. An internet connection is available on the driving monitoring system, and it can build a connection with the car owner through Telegram and Ubidots.